Infant Behavior and Competence Following Prenatal Exposure to a Natural Disaster: The QF2011 Queensland Flood Study. (6th March 2019) - Lequertier, Belinda; Simcock, Gabrielle; Cobham, Vanessa E.; Kildea, Sue; King, Suzanne
Abstract : This study utilized a natural disaster to investigate the effects of prenatal maternal stress (PNMS) arising from exposure to a severe flood on maternally reported infant social–emotional and behavioral outcomes at 16 months, along with potential moderation by infant sex and gestational timing of flood exposure. Women pregnant during the Queensland floods in January 2011 completed measures of flood‐related objective hardship and posttraumatic stress (PTS). At 16 months postpartum, mothers completed measures describing depressive symptoms and infant social–emotional and behavioral problems ( n  =   123) and competence ( n  =   125). Greater maternal PTS symptoms were associated with reduced infant competence. A sex difference in infant behavioral problems emerged at higher levels of maternal objective hardship and PTS; boys had significantly more behavioral problems than girls. Additionally, greater PTS was associated with more behavioral problems in boys; however, this effect was attenuated by adjustment for maternal depressive symptoms. No main effects or interactions with gestational timing were found. Findings highlight specificity in the relationships between PNMS components and infant outcomes and demonstrate that the effects of PNMS exposure on behavior may be evident as early as infancy. Implications for the support of families exposed to a natural disaster during pregnancy are discussed.